ASSESSING THE ROLE OF MANAGEMENT ACCOUNTING IN STRATEGIC DECISION-MAKING AND ORGANIZATIONAL PERFORMANCE - Ucu Supriatna; Wawan Ichwanudin; Ijang Faisal (Journal of Jabar Economic Society Networking Forum, 2024)
Background: The central role of interest rates in macroeconomics cannot be overstated. Interest rates not only influence the economic landscape but also affect consumer spending, investment, and borrowing. Among these, consumer loan demand and bank profitability are two areas significantly impacted by fluctuations in interest rates. Banks adjust their lending practices, and consumers' borrowing behavior shifts according to the prevailing rates, which ultimately influences economic stability. Understanding these dynamics is crucial for both financial institutions and policymakers to craft effective strategies. Aims: This study aims to analyze the effect of interest rate changes on consumer loan demand and the profitability of commercial banks. It seeks to identify patterns, establish causal relationships, and propose actionable insights for financial institutions. Research Method: A mixed-method approach is adopted, employing both qualitative and quantitative data. Time-series analysis is conducted on historical data spanning the last two decades, incorporating macroeconomic variables and interest rate trends. In addition, surveys of consumer attitudes toward loans at different interest rate levels are analyzed to gauge demand sensitivity. Results and Conclusion: Preliminary findings suggest a significant inverse relationship between interest rates and consumer loan demand. Banks experience increased profitability in periods of higher interest rates, although at the cost of potential market contraction. Lower rates generally boost consumer loan demand, but the effects on profitability are more nuanced, depending on the type of loan products offered. Contribution: This research provides a comprehensive analysis of how shifts in interest rates influence consumer behavior and bank profitability. It contributes to a better understanding of how banks should tailor their lending strategies in response to rate changes and provides insights for policymakers on the broader economic implications of interest rate adjustments.